DEVELOPING AN EFFECTIVE TEACHING METHOD OF â€œTRANSLATIONâ€ - Sunardi, Dono (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2017)
The subject of â€œTranslationâ€ is commonly found in the curriculum of English Departments of many universities. This suggests the significance of translation as a targeted competence of the students in the parts of educators and curriculum-makers. As a competence, the skill and ability to translate is deemed important in todayâ€™s globalizing world where people of different languages and cultures search to meaningfully interact each other. And yet, what is much needed is efforts to create effective methods of teaching â€œTranslation,â€ which includes among others the creation of class syllabus of â€œTranslationâ€ that connects a good mastery of linguistic, translation, and cultural theoretical aspects with translation practices and that bridges the factual needs for translation with the interest and talent of students. The data for this article were accumulated from teachers and practitioners of translation. The former refers to university lecturers who studied translation for their degrees. The practitioners are full-fledged members of Indonesian Translator Association (HPI). This guarantees the validity and solidity of the data. One finding this article presents is that in order to be effective the subject of â€œTranslationâ€ should contain a mix of approximately 40:60 of theoretical discussion and practice of translation. With this mix, as exemplified by the syllabus this article presents, the students are introduced to both declarative (know-what) and procedural (know-how) competences related of the field of translation. And with these, the students effectively learn to become a well-round translator.Key words: teaching methods, theoretical discussion, translation practicePENGEMBANGAN METODE PENGAJARAN â€œTRANSLATIONâ€ YANG EFEKTIFAbstrakMata kuliah â€œTranslationâ€ lazim dijumpai di dalam kurikulum Jurusan Bahasa Inggris di banyak universitas. Hal ini mengisyaratkan kesadaran pihak pendidik dan pembuat kurikulum menyangkut signifikansi penerjemahan sebagai salah satu kompetensi yang diharapkan dikuasai oleh mahasiswa. Sebagai kompetensi, keterampilan dan kemampuan untuk menerjemahkan dipandang penting dalam dunia yang mengglobal dewasa ini, di mana orang dari berbagai bahasa dan budaya yang berbeda berinteraksi secara bermakna. Meskipun demikian, yang sangat dibutuhkan adalah upaya untuk menyusun metode pengajaran â€œTranslationâ€ yang efektif, yang antara lain mencakup penyusunan silabus â€œTranslationâ€ yang mengaitkan pemahaman akan aspek-aspek teoritis kebahasaan, penerjemahan, dan budaya dengan praktik atau latihan penerjemahan dan yang menjembatani kebutuhan faktual akan penerjemahan dengan minat dan talenta mahasiswa. Data untuk artikel ini diperoleh dari para pengajar dan praktisi penerjemahan. Yang disebut pertama merujuk kepada para dosen yang secara formal belajar ilmu penerjemahan. Sementara itu, praktisi penerjemahan merujuk kepada anggota-anggota penuh Himpunan Penerjemah Indonesia (HPI). Ini menjamin bahwa data untuk artikel ini valid dan solid. Satu temuan yang dikemukakan oleh artikel ini adalah bahwa agar pengajaran â€œTranslationâ€ efektif diperlukan paduan antara diskusi teoritis dan latihan penerjemahan dengan rasio sekitar 40:60. Dengan paduan ini, sebagaimana dicontohkan oleh silabus yang juga disertakan di sini, mahasiswa diperkenalkan pada kompetensi deklaratif (paham-apanya) dan prosedural (tahu-bagaimananya) dari dunia penerjemahan. Dan dengan ini, mereka secara efektif dapat belajar menjadi penerjemah yang andal.Kata kunci: metode pengajaran, diskusi teoritis, praktik penerjemahan